Kartu Tanda Penduduk: Penantian Panjang Transpuan atas Akses Keadilan dan Kesetaraan - Theresia Sri Endras Iswarini (Yayasan Jurnal Perempuan, 2021)
The Population Administration Law (UU Adminduk) regulates that the Identity Card (Kartu Tanda Penduduk/KTP) is the states’ obligation facilitated by the Goverment and carried out by citizens. KTP is a tool to ensure that citizens are registered and their rights on civil, political and social economic are guaranteed. The absence of KTP causes multiple layers of vulnerability of stigmatized and discriminated groups, namely transwomen. They are marginalised from access to justice and basic rights, before and in a time of COVID-19 pandemic. Various stigma, violence and discrimination are experienced by transwomen who do not have access to KTP, which unfortunately does not anticipated by the Adminduk Law. This paper analyzes the implementation of the Adminduk Law related to KTP mechanism for transwomen, particularly in a time of pandemic. Using the women human rights framework, this paper shows substantive problems that potentially threaten access to justice and equality of transwomen.